Molecular Heterojunctions of Oligo(phenylene ethynylene)s with Linear to Cruciform Framework. (10th February 2015) - Wei, Zhongming; Hansen, Tim; Santella, Marco; Wang, Xintai; Parker, Christian R.; Jiang, Xingbin; Li, Tao; Glyvradal, Magni; Jennum, Karsten; Glibstrup, Emil; Bovet, Nicolas; Wang, Xiaowei; et al.
Abstract : Electrical transport properties of molecular junctions are fundamentally affected by the energy alignment between molecular frontier orbitals (highest occupied molecular orbital (HOMO) or lowest unoccupied molecular orbital (LUMO)) and Fermi level (or work function) of electrode metals. Dithiafulvene (DTF) is used as substituent group to the oligo(phenylene ethynylene) (OPE) molecular wires and different molecular structures based on OPE3 backbone (with linear to cruciform framework) are achieved, with viable molecular orbitals and HOMO–LUMO energy gaps. OPE3, OPE3–DTF, and OPE3–tetrathiafulvalene (TTF) can form good self‐assembled monolayers (SAMs) on Au substrates. Molecular heterojunctions based on these SAMs are investigated using conducting probe–atomic force microscopy with different tips (Ag, Au, and Pt) and Fermi levels. The calibrated conductance values follow the sequence OPE3–TTF > OPE3–DTF > OPE3 irrespective of the tip metal. Rectification properties (or diode behavior) are observed in case of the Ag tip for which the work function is furthest from the HOMO levels of the OPE3s. Quantum chemical calculations of the transmission qualitatively agree with the experimental data and reproduce the substituent effect of DTF. Zero‐bias conductance, and symmetric or asymmetric couplings to the electrodes are investigated. The results indicate that improved fidelity of molecular transport measurements may be achieved by systematic studies of homologues series of molecular wires applying several different metal electrodes. Abstract : Molecular heterojunctions based on self‐assembled monolayers of oligo(phenylene ethynylene)s, which have linear to cruciform framework, are measured by conducting probe–atomic force microscopy. Different molecular orbitals are obtained by adding the electron donating redox‐active dithiafulvene as substituent group to the OPE3 backbone. The Fermi level of the atomic force microscopy tip is tuned by different metal coating (Ag, Au, and Pt).